Mandible Growth of Wistar Rats: Effects of Malnutrition during Lactation in Adulthood Mandibular Size - Degani Jr, Hugo Vieira de Melo; Babinski, Monique da Silva Dias; Ramos, Cristiane da Fonte; Degani, Viviane Alexandre Nunes; Pires, Lucas Alves Sarmento; Babinski, Marcio Antonio (Journal of Morphological Sciences, 2018)
Introduction Malnutrition is a world health issue; thus, it is imperative to know its effects during lactation. The aim of this study was to evaluate the effects of maternal protein restriction during lactation on the horizontal and vertical bone growth of the mandible, according to predetermined parameters.Material and Methods At parturition, Wistar rat dams were randomly assigned to the following groups: (1) control, which had free access to a standard laboratory diet containing 23% of protein; (2) protein energy-restricted, which had free access to an isoenergetic, protein-restricted diet containing 8% of protein; and (3) energy-restricted group, which received limited access to commercial diet containing 23% of protein. After 21 days, all pups received free access to a standard laboratory diet containing 23% of protein until their adulthood. Afterwards, the animals were euthanized under thiopental anesthesia and their mandibles were excised. The dimensions of the excised pup mandibles were measured directly with a digital caliper.Results The protein-restricted and the energy-restricted groups presented minor adulthood mandibular length in all parameters analyzed.Conclusion Our results provide original information regarding the mandibular growth and indicate that the maternal nutritional state during lactation can affect the development of mandibular growth. Moreover, our results indicated that the growth dysfunction could not be restored after normalization of the diet.
Keywords: lactation; malnutrition; mandible; growth and development; wistar rats